Hadith #1628 - Sunan Ibn Majah - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Anas ibn Malik; Kathir bin Zayd al-'Aslmy كثير بن زيد الأسلمي; Muhammad bin Ayoub al-Klaby محمد بن أيوب الكلابي أبو هريرة الواسطي (Sunan Ibn Majah)
the Messenger of Allah said: “Every important matter that does not start with praise of Allah, is devoid (of blessings).”
Grade: